Análise de ciclo de vida de tijolos de argila queimados, tijolos de solo-cimento, e tijolos de solo-cimento ecológicos - Fontes, Caio Sant’Anna (2018)
In this work, the Life Cycle Analysis (LCA) methodology was used to measure the environmental impacts of the production of three types of bricks, thus enabling a comparison of the results obtained for each one. In order to do so, Burnt Clay Bricks (TAQ), Soil-Cement Bricks (TSC) and Ecological Soil-Cement Bricks (TSCE) - which replaced part of the cement by blast furnace slag - were selected to be studied and compared to each other. The comparison aimed to demonstrate how advantageous, environmentally, is the production of the third of them in relation to the first two. In order to be able to perform the LCA, impact indicators were adopted, which served as a means to quantify the environmental impacts generated by the production of the bricks in their various manufacturing phases. The following impact classes were considered: acid rain, human toxicity, eutrophication, non-renewable energy and global warming. Life cycle inventories were performed for the three categories of bricks, and the input data used were secondary, since they were taken from the studies of Koroneos and Dompros and C. Chen. These inventories enabled the realization of Life Cycle Inventory Analyzes, which served as a way of identifying and quantifying the interactions between the life cycle of the bricks and the environment. The results obtained with the application of the impact indicators to the data from the Life Cycle Inventory Analysis were coherent and showed that the Ecological Soil-Cement Bricks really offers a superior performance to the other two bricks in the environmental aspect. Of the impact classes considered, global warming was considered to be the most significant impact of the Ecological Soil-Cement Brick when compared to other bricks. This situation is due to the fact that the production of this type of brick emits considerably less CO2, the main factor contributing to global warming with regard to the production of brick pieces